Sex-specific effects of long-term exposure to bisphenol-A on anxiety- and depression-like behaviors in adult mice. (February 2015) - Xu, Xiaohong; Dong, Fangni; Yang, Yanling; Wang, Yu; Wang, Ran; Shen, Xiuying
Highlights: Long-term BPA exposure increased anxiety and depression in males but not in females. BPA reduced the level of testosterone in the brain of male mice. BPA inhibited the expressions of GABA(A)α2 receptor and ERβ of hippocampus in males. Abstract: Humans are routinely exposed to low levels of bisphenol A (BPA), an environmental endocrine disruptor, which is widely used in the production of polycarbonate plastics. The effects of perinatal exposure to BPA have been shown to affect various aspects of social behaviors such as anxiety and depression in adult offspring. Because sex hormones play a critical role in neurobehavior in adulthood, it is possible that long-term exposure to BPA has widespread effects on these emotional behaviors in adulthood. In the present study, adult mice were exposed to BPA at dosages of 0.04, 0.4, 4, 40 mg kg −1 d −1 for 12 weeks. A behavioral assay was performed using the open field test (OFT), mirrored maze, the elevated plus maze (EPM), and the forced swim task. The results showed that, after exposure to BPA at 0.4–40 mg kg −1 d −1, the number of open arm entries and the time spent in them in the elevated plus maze task were reduced in males but increased in females, and thus eliminating or reversing sex differences in these behaviors. BPA at 0.04–40 mg kg −1 d −1 increased the immobility of male mice in the forced swimming test. Furthermore, BPA (0.4–40 mg kg −1 d −1 ) significantly decreased brain level of testosterone in males, but no significant influence was found in serum and the brain levels of estradiol in females. Western blot analysis further indicated that BPA at 0.4, 4, or 40 mg kg −1 d −1 significantly down-regulated the protein level of estrogen receptor β (ERβ) in the hippocampus of the adult males but not females, and inhibited the protein level of GABA(A)α2 receptor in hippocampus of males but promoted that of females. These results suggest that long-term exposure to BPA sex specifically affects anxiety- and depression-like behaviors in adult mice. Changes in the levels of GABA(A)α2 receptor and ERβ proteins of hippocampus might be associated with BPA-induced changes in these emotional behaviors.